2014
DOI: 10.1007/s13524-014-0289-6
|View full text |Cite
|
Sign up to set email alerts
|

Skewed Sex Ratios and Criminal Victimization in India

Abstract: Although substantial research has explored the causes of India’s excessively masculine population sex ratio, few studies have examined the consequences of this surplus of males. We merge individual-level data from the 2004–2005 India Human Development Survey with data from the 2001 India population census to examine the association between the district-level male-to-female sex ratio at ages 15 to 39 and self-reports of victimization by theft, breaking and entering, and assault. Multilevel logistic regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 75 publications
(91 reference statements)
0
25
1
Order By: Relevance
“…(). Other covariates derived from a low sex ratio might also be explored such as the ratio of unmarried males, under the ‘supply‐of‐offenders’ hypothesis (South et al ., ), the female migration rate (Khan, ) or figures on female dry thermal burn death as seen in Pandey et al . ().…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…(). Other covariates derived from a low sex ratio might also be explored such as the ratio of unmarried males, under the ‘supply‐of‐offenders’ hypothesis (South et al ., ), the female migration rate (Khan, ) or figures on female dry thermal burn death as seen in Pandey et al . ().…”
Section: Discussionmentioning
confidence: 95%
“…However, it is unclear which socio-economic indicators or some other covariates may be associated with dowry deaths. South et al (2014) found a surplus of male offenders correlated with gender violence. In the same way, and according to Mukherjee et al (2001), overall crime is expected to be associated with crimes against women.…”
Section: Dowry Deaths In Uttar Pradeshmentioning
confidence: 97%
See 3 more Smart Citations